Islam, Politics and Government - Kirmanj, Sherko (Taylor & Francis Group, 2008)
The relationship between Islam and politics has attracted considerable attention in recent years, and especially since the 11 September attacks.This paper examines this relationship and comprises an extensive review of the main sources of Islam. The principal aim is to assess arguments regarding the political nature of Islam, and it seeks to investigate whether or not Islam is inherently political.Islamists have used Islam as an ideological tool and also as a weapon to obtain power when they are in opposition. Additionally, they have given their authority a religious gloss when they are in government.Therefore, the second objective of the paper is to investigate the authenticity of their claims of the political nature of Islam.The paper asserts that the Koran and the Sunna are concerned mainly with ethical and moral issues and have little to say about politics and governance.